2022
DOI: 10.3389/fphar.2021.789688
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HCV Tannins From Plants Traditionally Used in West Africa and Extracted With Green Solvents

Abstract: Millions of people are still infected with hepatitis C virus (HCV) nowadays. Although recent antivirals targeting HCV proteins are very efficient, they are not affordable for many people infected with this virus. Therefore, new and more accessible treatments are needed. Several Ivorian medicinal plants are traditionally used to treat “yellow malaria”, a nosological category including illness characterized by symptomatic jaundice such as hepatitis. Therefore, some of these plants might be active against HCV. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…and Pericopsis laxiflora (Benth. ex Baker) Meeuwen were most effective against HCV at nontoxic concentrations, with IC 50 value 0.71 and 0.23 μg/mL, respectively, and the polyphenols, including tannins like procyanidin A2, were the most effective constituents of the crude extracts (Bamba et al, 2022). Another study demonstrated the anti‐HCV potential of the Meli.…”
Section: Plant Constituents With Anti‐hcv Propertiesmentioning
confidence: 99%
“…and Pericopsis laxiflora (Benth. ex Baker) Meeuwen were most effective against HCV at nontoxic concentrations, with IC 50 value 0.71 and 0.23 μg/mL, respectively, and the polyphenols, including tannins like procyanidin A2, were the most effective constituents of the crude extracts (Bamba et al, 2022). Another study demonstrated the anti‐HCV potential of the Meli.…”
Section: Plant Constituents With Anti‐hcv Propertiesmentioning
confidence: 99%
“…We selected 15 plants and screened their extracts against HCV. The most active extracts were further studied to specify their IC 50 and toxicity in vitro, and several tannins were shown to be active 1 . We screened the same 15 crude extracts against HCoV-229E, a coronavirus associated with common cold.…”
mentioning
confidence: 99%